Teacher trust in others and teacher commitment co-mediate the path from school leadership to students’ reading literacy in rural Chinese schools - Zhu, Haixue; Li, Ling; Li, Hui (Frontiers in Psychology, 2022)
This study aimed to understand how teacher trust in others and teacher commitment co-mediate the path from school leadership to students' reading literacy. Altogether 1223 Grade 8 students (female =647; male = 576, Mage =15.35, SD = 1.28) and their 34 principals from 34 secondary schools in rural western China were sampled and matched. All the students completed the Program for International Student Assessment (PISA 2008) reading tests, and their principals completed the Leading and Teaching in Schools Survey Scale online which the variables of school leadership, teacher trust in others, and teacher commitment were evaluated. In addition, the “many to many” step was employed to match principals’ data with the students’ data by STATA analysis. The results indicated that: (1) there were direct and indirect effects of school leadership on student reading literacy in the mediation model; (2) the serial mediation of teacher trust in others and teacher commitment was significant between school leadership and reading literacy. This finding implies that enhancing teacher trust in others and teacher commitment in rural schools will help improve student's reading literacy.